DETERMINAN NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Saputro, Ilham Fajar Eko; Kamaluddin, Nurhadi (Universitas Multimedia Nusantara, 2025)
Abstract — The main objective of this study is to investigate the effect of profitability on firm value, as well as to examine the moderating function of the independent board of commissioners in this relationship. This study is motivated by the urgency of firm value as the main benchmark for investors, as well as the inconsistency of previous empirical findings regarding the relationship between profitability and firm value. The novelty of this study lies in the formulation of a moderation model that combines profitability variables and the structure of the independent board of commissioners, with a coverage of 139 manufacturing companies listed on the Indonesia Stock Exchange in the period 2020 to 2024. The sampling technique was carried out using purposive sampling. This study uses a quantitative approach by applying interaction analysis techniques through Moderated Regression Analysis (MRA). The results of the study show that profitability has a positive and significant effect on firm value, and the presence of an independent board of commissioners is proven to strengthen this effect. This finding confirms that the combination of solid profitability and good governance mechanisms is a crucial signal for investors in the investment decision-making process. Keywords: Profitability; Board of Commissioners; Company Value.